Species diversity, canonical correspondence, and phenetic analysis of microalgae in the Tancak Maesan River, Bondowoso, Indonesia - SULIFAH APRILYA HARIANI; ANGGUN RESTU KURNIAWATI; ABDU ROHMAN; YUNANTA CHANDRA BUANA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hariani SA, Kurniawati AR, Rohman A, Buana YC. 2025. Species diversity, canonical correspondence, and phenetic analysis of microalgae in the Tancak Maesan River, Bondowoso, Indonesia. Biodiversitas 26: 5612-5625. Microalgae are microscopic autotrophic organisms that inhabit various aquatic environments, including the Tancak Maesan River, Bondowoso, Indonesia. They play an essential role as primary producers in aquatic ecosystems and serve as bioindicators of water quality. Anthropogenic activities within the area may influence the microalgal community. The high diversity of microalgae also reflects considerable morphological variation among species. Due to their morphological plasticity and the limited availability of identification keys, morphological and anatomical characterization is crucial for phenetic analysis. This study aimed to analyze the diversity and phenetic characteristics of microalgae found in the Tancak Maesan River. Eleven species were identified, belonging to three divisions (Ochrophyta, Charophyta, and Chlorophyta). Navicula sp. had the highest density across all sampling sites. The diversity index indicated a moderate category (H? = 2.0906). The evenness index shows a high value (E = 0.8386), while the dominance index falls into a low category (D = 0.1436). Canonical Correspondence Analysis revealed that two microalgal species (Cymbella sp. and Pinnularia sp.) were strongly correlated with three abiotic parameters (pH, salinity, and Total Dissolved Solids). According to phenetic analysis, Achnanthes inflata and Navicula sp. cluster together with the highest similarity (Jaccard coefficient = 0.833). This study concludes that community activities and abiotic and anthropogenic conditions influence the presence of microalgae. The findings affirm the role of microalgae as sensitive bioindicators of water quality, responding to both natural and human-induced environmental changes. Consequently, this research establishes a crucial baseline for the river's microalgal diversity and underscores the importance of phenetic characterization for future ecological and monitoring studies.